ISOLATION, SCREENING AND IDENTIFICATION OF LACCASE PRODUCING FUNGI - ADIVEPPA BHEEMAPPA VANTAMURI; BASAPPA BASAWANNEPPA KALIWAL (International Journal of Pharma and Bio Sciences, 2015)
The enzyme laccase (p-diphenol: oxygenoxidoreductase; EC 1.10.3.2) is known to degrade many phenolic aromatic compounds. This enzyme is found in many plant species and is widely distributed in fungi including wood-rotting fungi where it is often associated with lignin peroxidase or manganese dependent peroxidase, or both. The objective of the present study was to isolate the potential fungus and characterize the organism with reverence to laccase production. About 150 fungal strains were isolated from natural habitat such as decaying wood, soil and mushrooms in the area of Dharwad and Uttara Kannada district. Karnataka, India and screened for their ability to produce laccase on solid medium containing 2, 2’-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS), Guaiacol, Tannic acid and Syringaldazine. Among 150 fungi isolated only 8 isolates have ability to produce laccase. Out of the 8 isolates, one (FS6) was presumed to be potent, another (FS1) showed medium potency and six (FS2, FS3, FS4, FS5, FS7 and FS8) showed week laccase producing ability. The FS6 was identified by conventional and molecular methods. Fungal DNA was extracted, ITS-rDNA amplified by PCR, and PCR amplification of the 18S rDNA were performed and its nucleotide sequence was done at BLAST-n site at NCBI server. ITS regions were sequenced. Based on the molecular characterization, the laccase producing novel isolate was identified as Marasmius sp. BBKAV79 (Accession no. KP455496, KP455497).